PENGARUH BEBAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN - Malihatus Sa'diah, Malihatus Sa'diah; Helmita, Helmita; Yusda, Desi Derina (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), 2025)
This study aims to determine the effect of workload and work environment on employee performance at Perum DAMRI Lampung Branch. In a dynamic work environment, workload and workplace conditions are key factors that influence employee productivity. This research uses a quantitative approach with a survey method and questionnaire as the data collection instrument. The population in this study includes all administrative employees of Perum DAMRI Lampung Branch, with a sample size of 62 respondents. Data analysis was conducted using validity and reliability tests, multiple linear regression analysis, partial (t-test), and simultaneous (F-test) testing. The results show that workload has a positive and significant effect on employee performance. Similarly, the work environment also has a positive and significant effect on employee performance. Simultaneously, workload and work environment significantly affect employee performance, contributing 59.3%, while the remaining percentage is influenced by other factors outside this study. These findings highlight the importance of proportional workload management and a supportive work environment to improve employee performance. This study is expected to serve as a reference for Perum DAMRI management in formulating policies to enhance work quality and employee well-being.